Analyzing the benefits of reducing parking: improving public transportation to reduce parking demand and increase space for green infrastructure in Manhattan, Kansas - Biondolilo, Jena (Kansas State University, 2013)
Climate change and declining ecological health of urban environments are global issues of growing concern. In order to mitigate these issues we must reduce Greenhouse Gas emissions and increase green infrastructure solutions. One way of doing this is through improving public transportation and decreasing parking areas. In this study, Manhattan, Kansas was used to illustrate how improvements to public transportation can reduce parking demand and to show how excess parking can be transformed into green space to improve the ecological health of the city. First a review of literature and case studies related to increasing ridership of public transportation, reducing parking demand, and calculating ecologic and economic benefits was done. Then ArcGIS was used to analyze the existing public transportation in Manhattan, Kansas. Improvements to the existing transit system were developed and potential increase in ridership was calculated. ArcGIS was then used to analyze existing parking in Manhattan, Kansas. Excess Parking was determined based on current parking demand and predicted transit ridership. A suitability study was then done in ArcGIS to determine which parking areas should be converted into green space. The suitability map assisted in choosing four specific parking areas to redesign in detail to incorporate additional green space and tree cover. It was estimated that improving Manhattan’s bus system could double its ridership. It was also estimated that with improved public transit and parking planning, 30% of Manhattan’s parking could be eliminated. Converting 30% of Manhattan’s parking into green space would decrease runoff and pollutants from parking lots. Ecological valuation methods were used to calculate the benefits of converting parking into green space. It was found that integrating green space into parking lots would decrease stormwater runoff, mitigate the heat island effect, store carbon, improve air quality and may have social benefits as well.
Keywords: Public transportation; Transit; Parking; Ecologic benefits; Low impact development; Benefit analysis; Landscape Architecture (0390)